Some applications of the natural uranium isotopes238U and 234U in environmental studies - Bonotto, Daniel Marcos [UNESP] (My University, 2009)
238U is the principal isotope of natural U (99.72% abundance) and is the progenitor of the (4n+2) series of radioelements. The isotope 234U is radiogenic and the decay chain from 238U through 234U proceeds as follows: 238U (4.46 Ga, α) → 234Th (24.1 days, β-) → 234Pa (1.18 min, α) → 234U (248 ka, α) → . The isotopes 238U and 234U are in secular equilibrium in all minerals and rocks greater than one million years old and that are closed systems for U. The 234U/238U activity ratio (AR) is, therefore, unity in the bulk of such systems. However, rock/soil-water interactions frequently result in AR for dissolved uranium that is greater than unity. Various mechanisms have been suggested to interpret the generation of the elevated ARs in solution. For instance, the occurrence of enhanced chemical solution of 234U due to radiation damage to crystal lattices or to autoxidation from U4+ to U6+ resulting from the decay of the parent 238U, the alpha-particle recoil ejection of the 234U precursor, 234Th, into solution, or the presence of alpha-recoil tracks intersecting the surface of grains and providing paths of rapid diffusion for 234U. Thus, all these mechanisms imply on disequilibria conditions affecting 238U and 234U during rock/soil-water interactions and several models have been developed to apply them for the hydrogeochemical prospection of concealed uranium deposits or in environmental studies involving hydrological systems. For example, hydrological studies of groundwaters have utilized U contents and ARs data with the purpose of dating. The change of AR with time for dissolved U in a groundwater that has evolved to a stable U chemistry in a reducing environment has been modeled, where the AR change after such a reduced zone has been entered depends, among other factors, on the initial AR of the dissolved U in the groundwater on entering the reduced zone, and on the U content of the groundwater. Based on the isotope dilution analysis, the AR and U content data in groundwaters have been utilized to deduce their proportions in a mixture. The weathering processes verified in hydrographic basins have also been investigated considering the equilibrium/disequilibrium conditions between 238U and 234U in waters, soils and rocks occurring in the basin. This chapter reports some experiments conducted under controlled situations in the laboratory for verifying the radioactive equilibrium between 238U and 234U during rock-water interactions and their implications on environmental studies. © 2009 by Nova Science Publishers, Inc. All rights reserved.